2015
DOI: 10.1111/dmcn.12962
|View full text |Cite
|
Sign up to set email alerts
|

Injection frequency of botulinum toxin A for spastic equinus: a randomized clinical trial

Abstract: FAQRESULTS Forty-two children entered the trial with 21 participants randomized to each group.There were three withdrawals and two children received serial casting midway through the trial. There was no significant difference in passive dorsiflexion between 12-monthly and 4-monthly regimens (p=0.41). There were also no significant between group differences on secondary outcome measures. There were no serious adverse events -the rate was 1.2 adverse events per child per year in the 12-monthly group and 2.2 adve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 30 publications
0
31
0
1
Order By: Relevance
“…While the relationships between limbs in children with diplegia were statistically controlled for, the inclusion both of children with diplegia and of those with hemiplegia may pose a further limitation, as research suggests notable differences in response to BoNT-A injections and reinjection schedules with CP subtype. 24 This study was also limited by the lack of a comparison group; therefore causal links between BoNT-A exposure and alterations in non-injected muscle groups cannot be established. While clinical outcomes were assessed by clinicians, informal reporting of goal-based outcomes, and functional assessments (Timed Up and Go test and 6-min walk test), future research would benefit from a more comprehensive assessment of functional outcomes including muscle strength.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…While the relationships between limbs in children with diplegia were statistically controlled for, the inclusion both of children with diplegia and of those with hemiplegia may pose a further limitation, as research suggests notable differences in response to BoNT-A injections and reinjection schedules with CP subtype. 24 This study was also limited by the lack of a comparison group; therefore causal links between BoNT-A exposure and alterations in non-injected muscle groups cannot be established. While clinical outcomes were assessed by clinicians, informal reporting of goal-based outcomes, and functional assessments (Timed Up and Go test and 6-min walk test), future research would benefit from a more comprehensive assessment of functional outcomes including muscle strength.…”
Section: Discussionmentioning
confidence: 98%
“…However, the small sample size of children who received injections to the hamstrings prevented a full statistical analysis of this group, thus limiting the application of these results to single‐level BoNT‐A cases only. While the relationships between limbs in children with diplegia were statistically controlled for, the inclusion both of children with diplegia and of those with hemiplegia may pose a further limitation, as research suggests notable differences in response to BoNT‐A injections and reinjection schedules with CP subtype . This study was also limited by the lack of a comparison group; therefore causal links between BoNT‐A exposure and alterations in non‐injected muscle groups cannot be established.…”
Section: Discussionmentioning
confidence: 99%
“…There is a debate, however, about its overall clinical benefits. Two RCTs investigating BoNT‐A injection frequency concluded that yearly injection versus every 4 months achieved the same treatment outcomes for lower‐limb spasticity in children with CP . Substantial savings, in medical costs and cost to the families in time and travel, would be made if the BoNT‐A regimen was reduced from every 4 months to yearly injections.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, this is caused by spasticity or dystonia, and there is no fixed contracture of the gastrocsoleus . At this stage, non‐operative management is ideal and usually consists of a combination of injections of botulinum toxin A (BoNT‐A) and the use of ankle‐foot‐orthoses (AFOs) combined with a physiotherapy programme (Figs ,) . The effects of BoNT‐A on toe walking and overall gait are small but helpful in early childhood .…”
Section: Brain Lesions Spinal Lesions Musculoskeletal Deformities Amentioning
confidence: 99%